Pembuatan Peta Digital untuk Area Rawan Kecelakaan Menggunakan Metode Rational Unified Process - Deo Seti Aji; Muhammad Asep Subandri (Lembaga Pengembangan Kinerja Dosen, 2025)
Traffic accidents are a serious problem frequently experienced by road users. Accidents do not occur by chance, but are triggered by several factors such as human error, vehicle technical failure (mechanical failure), and poor road conditions. This study aims to design and build a multi-platform Digital Map System for Accident-Prone Areas aimed at assisting the performance of the Bengkalis Traffic Police and providing information to the public on Bengkalis Island. This system is expected to be an innovative solution in accident risk mitigation efforts by presenting accident-prone location data in real-time and easily accessible to various parties. The method used in this study is the Rational Unified Process (RUP), a software development method that is carried out in stages and repeatedly (iteratively). The stages in the RUP include inception, elaboration, construction, and transition, each of which aims to produce a system that suits user needs. Each iteration produces a version of the system that can be tested and evaluated, so that errors or deficiencies can be detected early and effectively corrected. The result of this research is a digital map system equipped with accident-prone location markers based on previous traffic accident data, an early warning system (notification), and integration with GPS devices for navigation. System testing shows that the application can run well on various platforms, including Android mobile devices and the web. The conclusion of this research shows that the developed system can be optimally used by the community, especially on Bengkalis Island, as a means of information and increasing user awareness of traffic accidents.